Our responsibility before history - Alzamora, Carlos (2000)
Points out that SELA's creation was a historical decision. Warns that ever since its inception the institution has been beseiged by a paralyzing contradiction which resulted from limiting its role to economic coordination between its members, leaving aside political harmonization. Opines that the government of the region can still face their collective responsibility before history and also grant SELA the role it deserves.